Representasi Kearifan Lokal dari Mimbar Gereja Protestan Maluku - Pattiserlihun, Selvone Christin; Patty, Febby Nancy; Tiwery, Weldemina Yudit; Warela, Siphora Blandina (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2025)
The pulpit is considered the throne of God's glory because it becomes a tool for delivering God's Words or sermons from the perspective of The Protestant Church in the Moluccas (PCM). The Sermon in worship is considered sacred, so the pulpit is the centre of attention in the church buildings' arrangement. This paper aims to describe and identify the meaning of the forms of pulpits in the architectural layout of most GPM church buildings. This qualitative research uses three data collection methods, namely direct and digital observations, and literature reviews. The selected data will be discussed using descriptive analysis and content analysis methods. The discussion in this paper refers to three findings. First, historical evidence confirms that PCM is a traditional church. Second, the pulpit used as the centre in arranging the worship space always uses forms of local wisdom such as traditional Maluku musical instruments, essential flora and fauna that live with the Maluku community in certain areas, and the livelihoods of the Maluku community. Third, local wisdom used as a pulpit in Maluku shows an intensive dialogue between traditional values and colonial Christianity that remains sustainable even in this post-modern civilization. In principle, PCM, as one of the mainstream churches that have long existed in Indonesia, still uses local wisdom symbols to represent a dialogue between religion and local community traditions.